PENGARUH KOMPETENSI, INDEPENDENSI DAN PENGALAMAN AUDITOR TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH (Studi Empiris Pada Inspektorat Provinsi Papua) - Yumame, Leli Piska; Asnawi, Meinarni; Larasati, Rudiawie (Jurnal Akuntansi, Audit, dan Aset, 2020)
This study aims to examine the effect of competence, independence, and experience on the auditquality of the inspectorate officials in Papua province. A common problem in this study is theexistence of audit findings that are not detected by the inspectorate apparatus as internal auditorsbut found by external auditors, the Supreme Audit Agency (BPK). Operationally, the researchvariables are elaborated into several indicators. The competency variables of the apparatus areelaborated into three indicators, namely mastery of accounting and auditing standards, insight intogovernment, and skills improvement programs. The variables of apparatus independence areelaborated into two indicators, namely personal disturbance and external interference. Theapparatus experience variable is elaborated into several indicators, namely: In terms of length ofwork as an auditor, and the number of audit tasks that have been carried out. The audit qualityvariable is elaborated into four indicators, namely: process quality, result quality, and follow-up onaudit results.The population of this study were officials from the Inspectorate of Jayapura City, Inspectorate, andPapua Province who also carried out regular inspections. Data were taken from questionnairesdistributed to respondents. The variables in this study are the independent variable (independent)competence (X1), independence (X2), and experience (X3), while the dependent variable(dependent) is the quality of the audit (Y). Data were analyzed using multiple linear regressionanalysis (multiple regression).The results showed that competence and experience had a positive and significant effect on auditquality, while the independence variable did not have a significant effect on audit quality. Thecoefficient of determination shows that together competence, independence, and experiencecontribute to the dependent variable (audit quality) by 55.1% while the remaining 44.9% isexplained by factors outside the model of this study.